The research on interface between lithuanian direct investment abroad and foreign trade flows - Kozlova, Anžela; Miečinskienė, Algita (Business, Management and Economics Engineering, 2016)
The scientific research results related to foreign trade and direct investment abroad (DIA) are discussed in the article. The relation of the direct investment abroad and foreign trade is still under the discussion as there is no clear answer whether foreign trade is supplemented or replaced by the direct investment abroad. Since 1997 the flows of the direct investment abroad increased greately in Lithuania. Consequently, it is important to define the link between the DIA and foreign trade considering each country separately. Direct investment abroad and trade links in Lithuania in 1997–2014 are analyzed in the article. The research analysis involves Lithuanian direct investments in the developed countries except some countries, such as Belorus, Russia and Ukraine. It is defined that there is a positive bilateral link between Lithuanian direct investment abroad and foreign trade. It is also observed the impact of general development of Lithuanian direct investment abroad (considering certain countries) on the countries economy itself – imports can exceed exports. Engle-Granger causality test is applied in the research paper for the purpose of defining the impact of the DIA on the import and export range.